Online Attendance and Leave Application Using Mobile Web-Based Location and Photo Coordination Validation (Application to the Housing, Residential Areas and Environment Office of Trenggalek Regency) - Arfan Safut Pranoto; Wahyu Sri Utami (Jurnal Indonesia Sosial Teknologi, 2024)
The development of an employee attendance system by utilizing online attendance with photos that are also used for employee leave applications. Online-based attendance systems and online leave applications are very useful for employees and companies. The problem raised in the background above, formulation of the problem is to build an employee online attendance and leave application using PHP and MySQL that are dynamic and structured to be more efficient. If this mobile web application is not made, it will be outdated to do a better absence because in this era all systems are very advanced and easy to use. In this research, what is used to create an attendance application is to use programming languages such as HTML, CSS, and PHP, and to make connections only by creating a database that will be used in creating what I will create.